Association of regional bioelectrical phase angle with physical performance: a pilot study in elite rowers - Campa, F.; Mascherini, G.; Polara, G.; Chiodo, D.; Stefani, L. (Muscles, Ligaments and Tendons Journal, 2021)
Background. This study aimed to examine the association between regional Phase Angle (PhA) and physical performance in athletes where the use of specific body segments is required. Methods. Sixteen elite-level rowers (13 male aged 17.6 ± 2.1 yr; 3 female aged 21.0 ± 4.4 yr) participated in this investigation. Raw bioimpedance parameters were obtained with a phase-sensitive 50 kHz bioelectrical impedance analysis (BIA) device and fat-free mass, percentage of fat mass (FM%), and arms and legs lean soft tissue (ALST and LLST, respectively) were estimated using specific BIA-equation developed for athletes. The time (2000t) and the mean power (MP) expressed during the 2000 m test performed on a rowing ergometer were measured. Results. The major findings of the study were that upper hemisome PhA (UPhA) were more strongly related with 2000t (R2 = 0.35, p = 0.015) and MP (R2 = 0.40, p = 0.009) than whole-body PhA. Additionally, not only UPhA maintained a significant relationship with 2000t (p = 0.001) and MP (p = 0.001), even after adjustment for the co-variables sex, ALST, and FM%, but the explained variance increased to R2 = 0.72 and R2 = 0.78, respectively. Conclusions. These results suggest that the regional PhA might be used as a tool for evaluating performance related parameters in sports where specific body segments are involved, preferring it to the whole-body measured value.